Pemanfaatan sistem informasi e-commerce dalam pemasaran hasil pertanian di Desa Bukit berbasis web - Sari, Fitri Widya; Napitupulu, Ilham Hidayah; Laoly, Yulifati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study examines the application of a web-based e-commerce information system for marketing agricultural products. It assesses farmers' satisfaction with this system. A quantitative descriptive method was employed, with data collected through interviews, questionnaires, documentation, and source triangulation. Data analysis utilized the RACE framework and consumer satisfaction theory to assess system effectiveness and user perceptions. The findings indicate that the e-commerce system has successfully expanded market reach, improved transaction efficiency, and enhanced farmer engagement in digital marketing channels. Farmers reported positive experiences using the platform, highlighting its accessibility, adequate information flow, and improved marketing outcomes. The study's implications suggest that digitizing agricultural marketing through e-commerce information systems can enhance distribution efficiency, improve the welfare of farmers in rural areas, and support a transition toward a more modern and sustainable marketing system.